Stroke Features, Risk Factors, and Pathophysiology in SARS-CoV-2–Infected Patients - Amir A. Mbonde, MBChB, MMed; Cumara B. O’Carroll, MD, MPH; Marie F. Grill, MD; Nan Zhang, MS; Richard Butterfield, MA; Bart M. Demaerschalk, MD, MSc, FRCP(C) (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2022)
Objective: To provide a comprehensive description of stroke characteristics, risk factors, laboratory parameters, and treatment in a series of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–infected patients admitted to Mayo Clinic hospitals in Rochester, Minnesota; Jacksonville, Florida; and Phoenix, Arizona, as well as the Mayo Clinic Health System. Patients and Methods: We retrospectively identified hospitalized patients in whom stroke and SARS-CoV-2 infection were diagnosed within the same 3-month interval between September 8, 2019, and December 31, 2020. and extracted data on all available variables of interest. We further incorporated our findings into the existing body of basic science research to present a schematic model illustrating the proposed pathogenesis of ischemic stroke in SARS-CoV-2–infected patients. Results: We identified 30 cases during the study period, yielding a 0.5% stroke rate across 6381 SARS-CoV-2–infected hospitalized patients. Strokes were ischemic in 26 of 30 individuals and hemorrhagic in 4 of 30. Traditional risk factors were common including hypertension (24 of 30), hyperlipidemia (18 of 30), smoking history (13 of 30), diabetes (11 of 30), and atrial fibrillation (8 of 30). The most common ischemic stroke mechanisms were cardioembolism (9 of 26) and cryptogenic (9 of 26). Intravenous alteplase and mechanical thrombectomy were administered to 2 of 26 and 1 of 26, respectively. The median (interquartile range) serum C-reactive protein, interleukin-6, D-dimer, fibrinogen, and ferritin levels were 66 (21-210) mg/L, 116 (8-400) pg/mL, 1267 (556-4510) ng/mL, 711 (263-772) mg/dL, and 407 (170-757) mcg/L, respectively, which were elevated in individuals with available results. Conclusion: The high prevalence of vascular risk factors and concurrent elevation of proinflammatory and procoagulation biomarkers suggest that there is an interplay between both factors in the pathogenesis of stroke in SARS-CoV-2–infected patients.